2019
DOI: 10.1097/gox.0000000000002401
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Ketorolac Administration Is Not Associated with Hemorrhage in Cranial Vault Remodeling for Craniosynostosis

Abstract: Background:Nonsteroidal anti-inflammatory drugs have been used as part of multimodal postoperative analgesic regimens to reduce the necessity of opioids. However, due to its effect on platelet function, there is a hesitation to utilize ketorolac postoperatively. The goal of this study is to analyze our experience utilizing ketorolac in patients who underwent major cranial vault remodeling (CVR) for craniosynostosis with an emphasis on postoperative hemorrhage and complications.Methods:A retrospective review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…As we have demonstrated previously, ketorolac is a safe medication in this population, and does not increase risk of bleeding or blood transfusions, and reduces the need for opioids. 28 Children treated with the ERAS protocol required less morphine/dilaudid and oral narcotics. Thus, this demonstrates the success of our perioperative protocol to provide opioid-sparing pain control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have demonstrated previously, ketorolac is a safe medication in this population, and does not increase risk of bleeding or blood transfusions, and reduces the need for opioids. 28 Children treated with the ERAS protocol required less morphine/dilaudid and oral narcotics. Thus, this demonstrates the success of our perioperative protocol to provide opioid-sparing pain control.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to give one over the other is at nursing discretion, as there is not a concern for postoperative hemorrhage. 28 Oxycodone and morphine are available and are given as needed at nursing discretion. Decision on which pain medication to utilize is nurse-driven and based on protocol parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the previously defined exclusion criteria, only 16 articles published between 2000 and 2022 were included (Fig. 1 ) [ 2 , 10 , 14 , 27 39 ]. A total of 18 articles were excluded for the following reasons: improper methods (meta-analysis/systematic review, case reports) n = 4, reported no outcomes of interest ( n = 4), no full text was found ( n = 2), non-craniosynostosis patients ( n = 2), and incomplete description of perioperative pain management protocol ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 441 (52%) patients were included in seven articles describing the complete intraoperative analgesic protocol [ 14 , 32 , 34 , 36 , 38 , 39 ]. Reddy et al reported eighty patients were placed into one of two groups, with 39 receiving intraoperative dexmedetomidine and 41 who did not.…”
Section: Resultsmentioning
confidence: 99%
“…As a first-generation non-steroidal anti-inflammatory drug (NSAID), Ketorolac exerts its actions by blocking the prostaglandin synthesis by inhibiting the cyclooxygenase enzyme ( 22 , 23 ). The role of NSAIDs in controlling postoperative pain after LC has been studied in several studies.…”
Section: Introductionmentioning
confidence: 99%